Achievement goal viewed from parental involvement - Muttaqin, Fuzta Fauzal; Soetjipto, Helly Prajitno (Universitas Pendidikan Ganesha, 2020)
Parent involvement is a concept which includes children’s education. Research and theories suggest that parent involvement can predict children’s achievement goal. The aims of this research is to know whether parent involvement can predict the children’s achievement goal. Yogyakarta high-school students (185 males and 379 females) were selected to fill in two questionnaires which assessed both their perceptions of parent involvement and the students’ achievement goals. SEM analyses showed that the model was fit to explain the correlation between parent involvement and achievement goal. Results of this study revealed that parent involvement is a predictor of students’ achievement goals. Parent involvement had an indirect effect on mastery goals and performance goals also in approach and avoidance. Parent involvements’ effect on performance is higher than the effect on mastery. Parent involvements’ effect on approach is higher than the effect on avoidance. Implications of these findings for students’ achievement goal and academic achievement are discussed.